Mayoras y Mayores comunales (2022)
The indigenous peoples in Colombia within their historicity have gestated forms of existence from doing, being and remaining, through organizations which build their own government from within the communities reflected in the consolidation of an indigenous reservation. From this point of view, the present decolonial doing since Alexander Ortiz configures and emerges from the notion of "investigating" creating new-other decolonial ways of building knowledge from the voices, the feelings, the thinking and the knowledge of the actors, this is result of a collective reflection, conceiving a horizontal relationship with the indigenous community belonging to the Pijao people and as decolonial mediators, in such a way that new, "other" ways of sustaining the knowledge of the other are understood, with the objective of contemplating From the knowledge of the Pijao Los Angeles Indigenous Reserve, the contributions of Mayoras and Elders to the construction of communality based on sociocultural practices for the contribution to collective memory. Where the result was obtained, the transmission of ancestral knowledge that majorities and elders contribute from sociocultural practices to the construction of communality